2023
DOI: 10.1108/jfra-02-2023-0107
|View full text |Cite
|
Sign up to set email alerts
|

Board characteristics and ESG disclosure in energy industry: evidence from emerging economies

Yusuf Nuhu,
Ashraful Alam

Abstract: Purpose This paper aims to investigate the impact of board characteristics on environmental, social and governance (ESG) disclosure in the energy industry of emerging economies. Design/methodology/approach The authors adopt the Bloomberg ESG rating to measure the extent of ESG disclosure using a sample of 1,260 observations from BRICS emerging economies. Multiple regression techniques were used to estimate the effect of board characteristics on ESG disclosures of a sample Brazil, Russia, India, China, and So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 107 publications
1
5
0
1
Order By: Relevance
“…Embracing gender diversity in boardrooms can lead to tangible improvements in ESG performance, reflecting a commitment to promoting equality, diversity, and sustainability within organizations (Romano et al, 2020;Zahid et al, 2020). This conclusion about gender diversity aligns with research conducted by Bigelli et al (2023) and Nuhu & Alam (2024),which concluded that gender diversity significantly contributes to achieving higher ESG scores. In contrast, Abdelkader et al (2024) concluded a negative relationship between Board Gender Diversity and ESG.…”
Section: Gender Diversity and Esg Scoressupporting
confidence: 65%
See 2 more Smart Citations
“…Embracing gender diversity in boardrooms can lead to tangible improvements in ESG performance, reflecting a commitment to promoting equality, diversity, and sustainability within organizations (Romano et al, 2020;Zahid et al, 2020). This conclusion about gender diversity aligns with research conducted by Bigelli et al (2023) and Nuhu & Alam (2024),which concluded that gender diversity significantly contributes to achieving higher ESG scores. In contrast, Abdelkader et al (2024) concluded a negative relationship between Board Gender Diversity and ESG.…”
Section: Gender Diversity and Esg Scoressupporting
confidence: 65%
“…Bhatia & Marwaha (2022) examined the influence of board independence, board size, board gender diversity, CEO duality, and female executive participation on ESG disclosure scores in Indian companies and found that only CEO duality was a consistent factor in influencing the ESG Disclosure Score. Nuhu & Alam (2024) found that board gender diversity, board composition, and board diligence positively relate to the level of ESG disclosure, while the study documents no relationship between board size and ESG disclosure. Shaukat et al (2016) found that the greater the CSR orientation of the board (as measured by the board's independence, gender diversity, and financial expertise on the audit committee), the more proactive and comprehensive the firm's CSR strategy, and the higher its environmental and social performance.…”
Section: Board Attributes and Esg Scoresmentioning
confidence: 69%
See 1 more Smart Citation
“…This special issue covers several topics addressing different issues of sustainability accounting in the energy industry. The first article is titled "Board characteristics and ESG disclosure in energy industry: Evidence from emerging economies" by Nuhu and Alam (2023). It focuses on investigating the impact of board characteristics on environmental, social and governance (ESG) disclosure in the energy industry of emerging economies.…”
Section: Articles Reviewmentioning
confidence: 99%
“…Ukuran board berhubungan negatif dengan pengungkapan lingkungan, menurut beberapa penelitian sebelumnya (Akbas, 2016b;Osazuwa dkk., 2016;Pisano dkk., 2022). Hubungan antara karakteristik dewan dan pengungkapan lingkungan telah dipelajari di berbagai negara, termasuk Nigeria, India, Turki, dan negara-negara berkembang (Akbas, 2016b;Amalia dkk., 2022;Kumari dkk., 2022;Nuhu & Alam, 2023;Osazuwa dkk., 2016). Temuan ini secara konsisten menunjukkan bahwa ukuran dewan memiliki dampak negatif terhadap pengungkapan lingkungan (Akbas, 2016b;Osazuwa dkk., 2016;Pisano dkk., 2022).…”
Section: Pengaruh Variabel Kontrol Dan Pengungkapan Lingkunganunclassified